A Study on Constraints in People’s Participation in Integrated Watershed Development (Indian Journal of Extension Education, 2013)
Astudy conducted in Ahmednagar district of Maharashtra, where the famous Anna Hazare’s Ralegaon Siddhi was located, a series of constraints were identified in various stages of watershed development process. The major constraints were: lack of agreement on identification and prioritization of felt needs and unfelt needs, lack of conviction among some villagers to envisage the possible benefits to be accrued through watershed development activities in the initial stage, lack of technically qualified field assistants, inappropriate design of engineering solutions, neglect of technical matters in planning and design stage, lack of comprehensive understanding of the problem, field situation, appropriate technical solutions for watershed by government functionaries in planning stage, procedural delays in approvals, sanctions and fund disbursal, sanctioning power limitations and hierarchy issues, non-availability of funds at the time when most needed, and poor quality materials and hence poor quality soil conservation and check dams engineering works in the implementation stage. In the post-implementation stage, lack of post-implementation budgets for maintenance and sustainable management of watersheds was a major constraint. Among the suggestions given by respondents for better watershed management, the most important were: specific measures for human development including good and dedicated leadership, decision by consensus of all stakeholders, encouraging people to take own initiatives and not rely on government for everything, using community pressure for those who do not adhere to group decisions, empowering women with self help groups, and engaging youth in constructive activities. Among the economic and ecological measures, encouraging dairying to augment farm incomes, banning open grazing, tree felling, undertake massive tree plantation and among the water conservation measures, forming water cooperatives, using water judiciously and arresting flow of water wherever possible were suggested.